(untitled) (Journal of the College of Basic Education, 2022)
The science teacher preparation curriculum in basic education faculties is a pedagogically methodical system. An integrated person who works to develop the personality of the inputs during the operations to make them qualified outputs for the profession. Education, as it includes objectives, content, teaching methods, activities, means of evaluation, and upbringing. The process, the teaching staff, the students, the university building, the library, and the financial capabilities.